Penerapan Media Marhaban (Mading Bersama Hak dan Kewajiban) Untuk Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Pancasila Pada Siswa Kelas IV Sekolah Dasar - Wahyuni, Titin Tri; Rudyanto, Hendra Erik; Vivianingrum, Anita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
This research focused on the application of Marhaban media (Mading with Rights and Obligations) as a means of improving student learning outcomes in Pancasila Education subjects at SDN Bogem 1. The research used the PTK (Classroom Action Research) method including four stages, namely, planning, action, observation and reflection. The subject of the research was class IV SDN Bogem 1 which amounted to 9 students, including 6 male students and 3 female students. Instruments using interview sheets, question items, observation sheets and documentation. The results of learning improvement through the application of Marhaban (Mading with Rights and Obligations) media can be seen based on the pre-cycle class average score of 63.3 to 72.2 in cycle I, and 83.3 in cycle II. Students who reached the KKM increased from 33.4% to 55.5% in cycle I and to 88.8% in cycle II. The value of student learning outcomes that are below the KKM has decreased from 66.6% at the pre-cycle stage to 44.5% in cycle I and 11.2% in cycle II.